The scenary of community intervention - Lapalma, Antonio Ismael (Revista de Psicología, 2001)
This proyect present and analyses the elements for the construction of a "Scenario of Community Intervention" that enable to place the roles of the community psychologist into context.Cooperation alternative, alliances or confrontation between social actors are built as from the interrelation between the folowing aspects: a) social needs, b) social organization and c) environment and the linking of the processes of social participation.Four basic existing rationalities are shown in the intervention fiel such, politicals, technical, boreaucratic and the one related to the people. These aspect, examined in a determined social an historic context can be used as a tool for community diagnosis, strategic planning and assessment, from a participating perspective.